2014
DOI: 10.4251/wjgo.v6.i9.369
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction after pancreatoduodenectomy: Pancreatojejunostomyvspancreatogastrostomy

Abstract: Pancreatic surgeons try to find the best technique for reconstruction after pancreatoduodenectomy (PD) in order to decrease postoperative complications, mainly pancreatic fistulas (PF). In this work, we compare the two most frequent techniques of reconstruction after PD, pancreatojejunostomy (PJ) and pancreatogastrostomy (PG), in order to determine which of the two is better. A systematic review of the literature was performed, including major meta-analysis articles, clinical randomized trials, systematic revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Furthermore, a meta-analysis of 11 studies including 909 patients who underwent PG and 856 patients who underwent PJ published in 2019 by Jin Y et al [4] revealed that POPF incidence was substantially lower in the PG group than that in the PJ group, whereas the incidence of grade B and C fistula was not statistically different between the two groups. Other studies, however, have found no significant differences in the incidence of POPF, total morbidity, and death between the PG and PJ groups [17,18,19]. End-to-side duct-to-mucosa anastomosis or end-to-side invagination methods are used for PG anastomosis.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, a meta-analysis of 11 studies including 909 patients who underwent PG and 856 patients who underwent PJ published in 2019 by Jin Y et al [4] revealed that POPF incidence was substantially lower in the PG group than that in the PJ group, whereas the incidence of grade B and C fistula was not statistically different between the two groups. Other studies, however, have found no significant differences in the incidence of POPF, total morbidity, and death between the PG and PJ groups [17,18,19]. End-to-side duct-to-mucosa anastomosis or end-to-side invagination methods are used for PG anastomosis.…”
Section: Discussionmentioning
confidence: 98%
“…32 Most of the formerly published meta-analyses on pancreaticogastrostomy versus pancreaticojejunostomy conclude, however, that pancreaticogastrostomy is associated with a lower rate of POPF. [33][34][35][36][37][38][39][40][41][42][43][44][45][46] The rich blood supply, anatomical apposition, wider lumen and thicker wall of the stomach compared to the jejunum are arguments mentioned in favor of pancreaticogastrostomy. [47][48][49] This is partially in line with the results, although the current meta-analysis is updated with the latest RCT on this subject, which proves otherwise.…”
Section: Hpbmentioning
confidence: 99%
“…In some cases, pancreaticogastrostomy (PG) is performed, in which instead of joining to jejunum, the pancreatic stump is invaginated to the stomach lumen [ 12 ]. Although both PG and DPJ are preferred over DTM anastomosis when the pancreatic duct is very small, studies have shown that there is no significant difference in the rate of POPF between different anastomotic techniques [ 13 - 15 ] and none of the technical variations of PJ or PG anastomosis has been found to be consistently superior to another [ 16 ]. Currently, DTMPJ remains the anastomosis of choice after PD in many centers worldwide.…”
Section: Introductionmentioning
confidence: 99%